Analisis Hubungan Faktor Determinan dengan Tindakan Pencegahan Penyakit Rabies di Sepauk - Agus Samsudrajat. S; Eka Hariani; Hapsari, Dian Indahwati Hapsari; Agustina, Agustina (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Rabies is a disease with a Case Fatality Rate (CFR) or a mortality rate of up to 100%. According to data from the World Health Organization (WHO) in 2018, an estimated 55,000 deaths in the world are caused by this disease. Based on an annual report prepared by the West Kalimantan Provincial Health Office, in 2022 there were 286 cases of bites by rabies-transmitting animals with 2 deaths, one of which was at the Sepauk Health Center. This study aims to analyze the factors associated with the prevention of rabies in the Sepauk Health Center. This research is a quantitative design with a case control approach. The number of samples is 120 respondents with Accidental Sampling technique. The statistical test used was square-test with a 95% confidence level.The results showed that there was a significant relationship with knowledge p value = 0.022, OR = 2.854, attitude p value = 0.012, OR = 2.954, support from community leaders p value = 0.022, OR = 2.889, role of health workers p value = 0.009, OR = 3.029, and the role of animal health workers (p value = 0.011, OR = 3.064 with Rabies disease prevention measures.It is suggested to the government to improve information/counseling related to rabies, to collect HPR data, and to always provide anti-rabies serum needs if there are cases. Kata Kunci      : Rabies, Gigitan, GHPR, Kesehatan Hewan